2008
DOI: 10.1111/j.1365-2966.2008.13226.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling interaction of relativistic and non-relativistic winds in binary system PSR B1259−63/SS2883 – I. Hydrodynamical limit

Abstract: In this paper, we present a detailed hydrodynamical study of the properties of the flow produced by the collision of a pulsar wind with the surrounding in a binary system. This work is the first attempt to simulate interaction of the ultrarelativistic flow (pulsar wind) with the non‐relativistic stellar wind. Obtained results show that the wind collision could result in the formation of an ‘unclosed’ (at spatial scales comparable to the binary system size) pulsar wind termination shock even when the stellar wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
209
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(226 citation statements)
references
References 54 publications
15
209
1
1
Order By: Relevance
“…The shocked wind flows away from the companion star forming a comet-like tail of emission. Relativistic hydrodynamical calculations show the flow is conical with an opening angle set by η and can reach highly relativistic speeds (Bogovalov et al 2008). High energy electrons emit VHE gamma-rays and synchrotron X-rays close to the pulsar and lose energy as they flow out, emitting in the radio band far from the system (Dubus 2006).…”
Section: Relativistic Doppler Boostingmentioning
confidence: 99%
See 1 more Smart Citation
“…The shocked wind flows away from the companion star forming a comet-like tail of emission. Relativistic hydrodynamical calculations show the flow is conical with an opening angle set by η and can reach highly relativistic speeds (Bogovalov et al 2008). High energy electrons emit VHE gamma-rays and synchrotron X-rays close to the pulsar and lose energy as they flow out, emitting in the radio band far from the system (Dubus 2006).…”
Section: Relativistic Doppler Boostingmentioning
confidence: 99%
“…An offset of 0.275 should be added to the above phases to compare with the radio-based ephemeris of LS I +61 • 303. Bogovalov et al (2008) carried out relativistic hydrodynamical simulations of a pulsar wind interacting with a stellar wind with the specific case of PSR B1259-63 in mind. They found that the shocked pulsar wind can accelerate from bulk Lorentz factors ≈1 close to the termination shock up to 100 far away.…”
Section: Psr B1259-63mentioning
confidence: 99%
“…An important parameter that characterizes the wind interaction region is the pulsar to stellar wind momentum flux ratio (e.g. Bogovalov et al 2008):…”
Section: Physical Scenariomentioning
confidence: 99%
“…The distance between the CD and the star is then ≈2.3 × 10 12 cm. The CD, which separates the shocked stellar and pulsar winds, has an asymptotic half-opening angle (see Bogovalov et al 2008 and references therein):…”
Section: Physical Scenariomentioning
confidence: 99%
“…Electrons accelerated in the shock between the PW and stellar wind can produce synchrotron radiation and/or upscatter stellar or disk photons from LS2883to produce inverse-Compton (IC) radiation (Tavani & Arons 1997;Kirk et al 1999;Dubus 2006;Bogovalov et al 2008;Khangulyan et al 2011;Kong et al 2011;Takata et al 2012;Mochol & Kirk 2013). The unshocked PW particles may also generate γ-rays (Khangulyan et al 2012).…”
Section: Introductionmentioning
confidence: 99%